Exploring Junior High School Science Teachers' Perceptions of Science Scientists, Science Subjects, NOS, and NOSI - Fitratunisyah; PRELIA DWI AMANAH; Lia Saptini Handriani; Thufail Mujaddid Al-Qoyyim; Eka Muliati; Muhammad Tantawi Jauhari; A Wahab Jufri (Postgraduate Program, University of Mataram, 2025)
This research aims to explore junior high school science teachers' perceptions of scientists, science subjects, the nature of science (NOS), and the nature of scientific inquiry (NOSI). Using a quantitative descriptive approach, this research involved 61 junior high school science teachers from various regions in Indonesia. A research instrument was developed, which included needs analysis, instrument design, instrument development, and instrument evaluation. The research results show that junior high school science teachers have mixed perceptions of scientists, with the majority recognizing the important role of scientists in the advancement of science and technology. However, there is a diversity of views regarding the physical and demographic characteristics of scientists. Regarding science subjects, teachers tend to have a positive perception of science's ability to develop students' critical and creative thinking skills. Teachers' perceptions of NOS show that most teachers understand the tentative nature of scientific knowledge and the importance of empirical evidence in science. Meanwhile, perceptions of NOSI show that teachers understand that scientific inquiry starts from curiosity about the natural environment, although there are variations in their beliefs regarding the effectiveness of inquiry models in learning. These findings emphasize the importance of ongoing professional development for teachers to increase their understanding of NOS and NOSI, as well as improve the quality of science learning in secondary schools.